2004
DOI: 10.1002/jssc.200401918
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrophoretic and micellar electrokinetic separations of asymmetric dimethyl‐L‐arginine and structurally related amino acids: Quantitation in human plasma

Abstract: We report the development of efficient electrophoretic methods for the separation and quantification of L-arginine and six naturally occurring derivatives that are structurally and functionally related. Capillary electrophoresis (CE) employing a concentrated borate buffer at pH 9.4 achieves the separation of mixtures containing dimethyl-L-arginine, NG-monomethyl-L-arginine, L-arginine, L-homoarginine, L-ornithine, and L-citrulline as 4-fluoro-7-nitrobenzofurazan derivatives. In addition, the separation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 17 publications
1
22
1
Order By: Relevance
“…As previously indicated (see Section 2.2), the analysis in CSF of sulfur-containing excitatory amino acids in the presence of neurotransmitters Glu and Asp was performed by Becker et al [58] in 0.1 M borate, 50 mM SDS, and 5% v/v MeOH. Trapp et al [97] have suggested the use of 250 mM borate buffer containing 50 mM SDS to obtain the separation of mixtures containing dimethyl-L-Arg, monomethyl-L-Arg, L-Arg, L-homoArg, L-Orn, and L-Cit as 4-fluoro-7-nitrobenzofurazan derivatives. The addition of deoxycholic acid to the same running buffer allowed also the separation of the isomeric dimethyl-L-Arg (symmetric and asymmetric) derivatives.…”
Section: Amino Acids In Biological Fluidsmentioning
confidence: 99%
“…As previously indicated (see Section 2.2), the analysis in CSF of sulfur-containing excitatory amino acids in the presence of neurotransmitters Glu and Asp was performed by Becker et al [58] in 0.1 M borate, 50 mM SDS, and 5% v/v MeOH. Trapp et al [97] have suggested the use of 250 mM borate buffer containing 50 mM SDS to obtain the separation of mixtures containing dimethyl-L-Arg, monomethyl-L-Arg, L-Arg, L-homoArg, L-Orn, and L-Cit as 4-fluoro-7-nitrobenzofurazan derivatives. The addition of deoxycholic acid to the same running buffer allowed also the separation of the isomeric dimethyl-L-Arg (symmetric and asymmetric) derivatives.…”
Section: Amino Acids In Biological Fluidsmentioning
confidence: 99%
“…L-ornithine, and L-citrulline as 4-NBD-F derivatives was achieved by Trapp et al [79] using a concentrated borate buffer at pH 9.4. In addition, the separation of the isomeric dimethyl-L-arginine derivatives (symmetric and asymmetric) was attained with baseline resolution by MEKC when a high concentration of deoxycholic acid is added like a surfactant to the same running buffer.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…The effect of ADMA infusion in humans and analytical approaches used in the quantification of ADMA have recently been reviewed [202,203]. Effective HPCE techniques for the quantification of L-arginine derivatives, including ADMA, in biomedical samples have been reported [204,205]. Example of CE-LIF analysis of ADMA in serum samples from healthy and memorialized human subjects are shown in Fig.…”
Section: Asymmetric Dimethylarginine (Adma)-adma Is a Biogenic Analogmentioning
confidence: 99%
“…Micellar electrokinetic chromatography (MEKC) is almost exclusively used for analysis of small molecules such as drug and their metabolites. MEKC is a very potent technique to determine small organic members of the NO pathway including L-arginine, ADMA and SDMA [204,205,241]. Other HPCE modes, including capillary isoelectric focusing (CIEF), capillary electrochromatography (CEC) and gel-sieving capillary electrophoresis generally used for separation of medium and large size molecules, and specific analytical tasks were not included in this review.…”
Section: High-performance Capillary Electrophoresis (Hpce) Of the No mentioning
confidence: 99%
See 1 more Smart Citation